Small Noncoding RNAs and Their Role in the Pathogenesis of Mycobacterium tuberculosis Infection - Ostrik, Albina A. (Biochemistry (Mosc), 2021)
Mycobacterium tuberculosis possesses a significant arsenal of strategies to combat immune defense of the host organism. Small noncoding RNAs, which constitute the largest group of regulatory RNAs, play an important role in the host–pathogen interactions and represent one of the levels of the regulation of interactions of microbial cells with their environment. The regulatory role of small RNAs in pathogenic bacteria is essential when rapid adaptation to the changing environmental conditions with further synchronization of metabolic reactions are required to ensure microbial survival and infection progression. During the past few years, eight small RNAs from M. tuberculosis have been functionally characterized, and targets for four of them have been identified. Small RNAs from M. tuberculosis and other pathogenic microorganisms were found to be one of the most important functional factors in the adaptive response to changing environmental conditions.